Creating novel ornamentals via new strategies in the era of genome editing - Jin, Chunlian; Dong, Liqing; Wei, Chang; Wani, Muneeb Ahmad; Yang, Chunmei; Li, Shenchong; Li, Fan (Frontiers in Plant Science, 2023)
Ornamental breeding has traditionally focused on improving novelty, yield, quality, and resistance to biotic or abiotic stress. However, achieving these goals has often required laborious crossbreeding, while precise breeding techniques have been underutilized. Fortunately, recent advancements in plant genome sequencing and editing technology have opened up exciting new frontiers for revolutionizing ornamental breeding. In this review, we provide an overview of the current state of ornamental transgenic breeding and propose four promising breeding strategies that have already proven successful in crop breeding and could be adapted for ornamental breeding with the help of genome editing. These strategies include recombination manipulation, haploid inducer creation, clonal seed production, and reverse breeding. We also discuss in detail the research progress, application status, and feasibility of each of these tactics.